Altered gut microbiota in erectile dysfunction patients: a pilot study - Su, Quanxin; Wang, Kenan; Luo, Yayin; Tang, Qizhen (Frontiers in Microbiology, 2025)
PurposeWith the growing body of research on gut microbiota in recent years, various potential associations between gut microbiota and health or disease have been identified. However, the role of gut microbiota in Erectile dysfunction (ED) remains poorly understood. This study aimed to compare the changes in gut microbiota and metabolic pathways between ED males and healthy control group, contributing to the exploration of ED pathogenesis.MethodsFecal samples were collected from 19 ED patients and 15 healthy controls (aged from 18 to 60 years), with erectile function assessed using the 5-item version of the International Index of Erectile Function (IIEF-5). Macro-genomic sequencing was performed on the NovaSeq PE 150 platform to characterize the gut microbiota distribution among the groups.ResultsNo significant differences in alpha diversity of the gut microbiota were observed between the ED and control groups. Additionally, Principal component analysis (PCA) analysis revealed no notable changes in microbiota composition between the two groups. A comparison of the abundance of key species showed that, in the ED group, species such as Ruminococcus gnavus, Thomasclavelia ramosa, Clostridium sp. AF32-12BH, Clostridium nexile, and Eubacterium siraeum were more abundant, while the abundance of Bacteroides intestinalis was decreased compared to the control group. Furthermore, pathways related to nucleotide and lipid metabolism were found to be highly expressed in the ED group.ConclusionThis pilot study found a decrease in the abundance of Bacteroides intestinalis and an increase in the abundance of Ruminococcus gnavus in the ED sample. These microbiota changes may contribute to ED by promoting atherosclerosis and inhibiting the degradation of branched-chain amino acids. In the future, it may be possible to achieve better outcomes for ED patients by precisely regulating the gut microbiota.